2020
DOI: 10.21203/rs.3.rs-20932/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Elucidation of the active compounds and molecular mechanisms of Smilacis Chinae Rhizoma for treatment of pelvic inflammatory disease based on network pharmacology and MMGBSA-docking

Abstract: Background Smilacis Chinae Rhizoma (SCR) is widely used in the treatment of pelvic inflammatory disease (PID). However, its active ingredients and the mechanisms against PID remain elusive. This study aimed to clarify the active ingredients and explore their molecular mechanisms on PID. Method Network pharmacology and MMGBSA-docking exploited the active compounds and mechanisms against PID, as well as validating the binding mode of candidate targets.Results Network pharmacology revealed 32 active compounds and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Zhang et al demonstrated that many bioactive constituents in food, including the aforementioned compounds, possessed potential anti-PID activity using the combined method of network pharmacology and MMGBSA-docking. 40 Therefore, it is also interesting to investigate whether other compounds in food possess anti-PID activity.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al demonstrated that many bioactive constituents in food, including the aforementioned compounds, possessed potential anti-PID activity using the combined method of network pharmacology and MMGBSA-docking. 40 Therefore, it is also interesting to investigate whether other compounds in food possess anti-PID activity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Many compounds besides engeletin in food possess an AR inhibitory effect, such as quercetin, resveratrol, and rutin. , Because AR is a potential target for the treatment of PID, whether these compounds also possess anti-PID activity is not known. Zhang et al demonstrated that many bioactive constituents in food, including the aforementioned compounds, possessed potential anti-PID activity using the combined method of network pharmacology and MMGBSA-docking . Therefore, it is also interesting to investigate whether other compounds in food possess anti-PID activity.…”
Section: Discussionmentioning
confidence: 99%